Fracture Toughness of Vinyl Ester Composites Reinforced with Sawdust and Postcured in Microwaves. (29th July 2012) - Ku, H.; Prajapati, M.; Trada, M.
Abstract : A commercial vinyl ester resin supplied by Hetron Chemical Pty. was reinforced with varying percentages by weight of sawdust. The sawdust particles were sieved into 3 different sizes, which were <300  μ m, 300–425  μ m, and 425–1180  μ m, respectively, with a view to increase its fracture toughness for civil and structural applications. The sawdust used varied from 0% w/t to 15% w/t in step of 5% w/t. For higher w/t% of sawdust, the mixture would be too sticky to be mixed and cast. The cast composites were cured in ambient conditions and then postcured in microwave irradiation. They were then tested for fracture toughness using short bar tests. The values of fracture toughness of the composites increased with increasing particulate size, and this is due to the size distribution of the filler. It was found that the optimum amount of sawdust (425–1180  μ m) was 15% w/t, with which the increase in fracture toughness was 126% as compared to neat resin and the reduction in cost was 15%. Furthermore, the optimum amount of sawdust (300–425  μ m) was also 15% w/t, with which the increase in fracture toughness was 28.3% as compared to neat resin and the reduction in cost was again 15%.